Tortilla Flat Restaurant and Motel - Richard Hoffstedt:::Creator::::::::::::
A sign advertises the Tortilla Restaurant and Motel. Tortilla Flat, Arizona is about 60 miles east of Phoenix The word 'motel' on the sign has been crossed out. This town in the Superstition Mountains was established in 1904, though the name for the area probably pre-dates it by several years. As of 2008, the population was 6.